SPECIFIC FEATURES OF TAXATION OF SELF -EMPLOYED PERSONS AND SMALL BUSINESSES (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
The article is devoted to a comprehensive analysis of the evolution, current state and future reforms of the taxation system for self-employed individuals and small businesses in the modern economic conditions of the Republic of Uzbekistan. The study examines the role of small businesses in ensuring macroeconomic stability based on the latest statistical data for 2023–2025, in particular, reports of the Statistics Agency of the Republic of Uzbekistan and the Tax Committee. The article provides a scientific and theoretical justification for the economic consequences of the income threshold of 100 million soums established for self-employed individuals, the effectiveness of digitalization of tax administration in reducing the shadow economy, and tax reforms planned for 2026 (reducing the turnover tax rate to 1 percent). The study also analyzes the differences between international experience and national practice in legalizing the segment of "hard-to-tax" entities. The results show that optimizing the tax burden and increasing fiscal transparency are key drivers of increased entrepreneurial activity